2022
DOI: 10.3390/vaccines10071097
|View full text |Cite
|
Sign up to set email alerts
|

First COVID-19 Booster Dose in the General Population: A Systematic Review and Meta-Analysis of Willingness and Its Predictors

Abstract: The emergence of breakthrough infections and new highly contagious variants of SARS-CoV-2 threaten the immunization in individuals who had completed the primary COVID-19 vaccination. This systematic review and meta-analysis investigated, for the first time, acceptance of the first COVID-19 booster dose and its associated factors among fully vaccinated individuals. We followed the PRISMA guidelines. We searched Scopus, Web of Science, Medline, PubMed, ProQuest, CINAHL and medrxiv from inception to 21 May 2022. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
50
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 85 publications
13
50
1
5
Order By: Relevance
“…Our findings were higher than the results of previously published meta-analysis by Norhayati et al, which reported a pooled proportion of COVID-19 vaccine acceptance from 170 studies in 50 countries of 61% (95% CI: 59–64%) [ 93 ]. A recently published systematic review and meta-analysis by Galanis et al estimated the acceptance of a COVID-19 vaccine booster dose at a level of 79%—similar to our estimate—among the general public based on the inclusion of 14 studies [ 107 ].…”
Section: Discussionsupporting
confidence: 69%
“…Our findings were higher than the results of previously published meta-analysis by Norhayati et al, which reported a pooled proportion of COVID-19 vaccine acceptance from 170 studies in 50 countries of 61% (95% CI: 59–64%) [ 93 ]. A recently published systematic review and meta-analysis by Galanis et al estimated the acceptance of a COVID-19 vaccine booster dose at a level of 79%—similar to our estimate—among the general public based on the inclusion of 14 studies [ 107 ].…”
Section: Discussionsupporting
confidence: 69%
“…The prevalence of individuals who ‘definitely intended’ to receive a booster vaccine was high in both samples (73% and 67%, respectively). Similar high rates of acceptance have been reported regarding the primary vaccine course, estimated at 84% (UK) and 82% (Australia) in one recent meta-analysis [ 13 ] and 67% (Europe) and 76% (Oceana) in another [ 32 ], and are comparable to a recent global estimate (79%) for booster intent [ 17 ]. However, to the best of our knowledge, the present study is the first to measure booster intentions in Australia specifically [ 17 ].…”
Section: Discussionsupporting
confidence: 77%
“…At present, however, very few studies have investigated the intention to receive a booster vaccine. A recent meta-analysis reported on just twelve studies that have investigated the predictors of booster intent, with the majority focusing on sociodemographic factors and limited to Asian samples [ 17 ]. Additionally, despite concern regarding the COVID-19 virus and positive perceptions of the COVID-19 vaccine (i.e., psychological perceptions) being some of the strongest predictors of the intention to receive a first COVID-19 vaccine, only five studies included predictors investigating the former, and four the latter.…”
Section: Introductionmentioning
confidence: 99%
“…No matter the type of COVID-19 vaccine administered, the waning of humoral responses is observed, especially in older adults, immunosuppressed individuals, and males [ 22 , 23 ]. Meanwhile, the willingness to receive a booster dose has decreased in communities, and “doubt on the necessity of further vaccination” is mentioned as the main reason [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%